Fiscal decentralization: A review of the Iraqi Constitution of 2005 - Ghali, Aad Ameer; Al-khafaji, Forqan Ali Hussein (Technium Social Sciences Journal, 2022)
Abstract. Every state needs something to suit its demands, whatever its form, and there is no disagreement over this; what matters is how to allocate revenues for the federal states. There is no specific way or ready model for distributing financial competencies between the federal government and the states, but it varies from state to state. Iraqi legislators adopted the method of political decentralization and regional administrative decentralization, as outlined in the Iraqi State Administration Law for the Transitional Period of 2004, and the Iraqi Constitution for the year 2005. There are many problems resulting from overlapping in jurisdictions or from the legislative insufficiency of a specific jurisdiction for a specific party. The concept of local development has outgrown its reliance on the central system that countries used in the 1960s and 1970s, and it can no longer be sustained in a rational manner. For the purpose of studying the subject from a legal point of view, we followed in this research the binary division approach, as the research was divided into two parts: the first section deals with the nature of administrative decentralization, and the second section deals with administrative decentralization in the Constitution of the Republic of Iraq for the year 2005, and in conclusion we reached several results and proposals We will mention it at the end of our research.